1992
DOI: 10.1001/archpsyc.49.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Plasma Norepinephrine Responsivity to Orthostatic Challenge in Anxiety Disorders

Abstract: Heart rate and plasma norepinephrine responsivity to a physiologic challenge, ie, orthostasis, were measured in 20 patients with panic disorder (PD) and 20 age- and sex-matched normal control subjects. While the two groups exhibited similar supine heart rates, patients with PD had a significantly greater heart rate response to orthostatic challenge. Plasma norepinephrine responses did not differ between patients with PD and normal control subjects. In a matched subgroup of 14 patients with PD, 14 normal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(14 citation statements)
references
References 63 publications
1
12
1
Order By: Relevance
“…An early study that included a mixed population of patients with either specific or generalized SAD found significantly elevated plasma norepinephrine levels in the patients with SAD compared with controls. 21 Later studies, however, found no significant differences in noradrenergic indexes in patients with generalized SAD, 17,22 although one 23 did find greater sympathetic arousal in patients with nongeneralized disease compared with those with the generalized subtype and healthy controls. Further investigation is needed to determine the role of the noradrenergic system in those with generalized SAD.…”
Section: Arch Genmentioning
confidence: 94%
“…An early study that included a mixed population of patients with either specific or generalized SAD found significantly elevated plasma norepinephrine levels in the patients with SAD compared with controls. 21 Later studies, however, found no significant differences in noradrenergic indexes in patients with generalized SAD, 17,22 although one 23 did find greater sympathetic arousal in patients with nongeneralized disease compared with those with the generalized subtype and healthy controls. Further investigation is needed to determine the role of the noradrenergic system in those with generalized SAD.…”
Section: Arch Genmentioning
confidence: 94%
“…However, given that the majority of studies reported normal plasma NE levels in PD (Cameron et al 1984(Cameron et al , 1987(Cameron et al , 1990(Cameron et al , 1996Albus et al 1986;Schneider et al 1987;Stein et al 1992; Gurguis and Uhde 1998), failure in mechanisms involving agonist-mediated regulation of gene expression of adrenergic receptors (Hadcock and Malbon 1993, and references therein) may provide alternate, more plausible explanations for the present findings. Protein kinase A (PKA) is of particular interest, because it mediates agonist-induced receptor phosphorylation and downregulation.…”
Section: Discussionmentioning
confidence: 62%
“…Panic disorder has been associated with autonomic dysreactivity [25,26,27,28,29,30]. It has also been reported that panic symptoms reappear in 42% of patients after hyperventilation, a maneuver that has been associated with the vasovagal reflex [31,32,33,34].…”
Section: Discussionmentioning
confidence: 99%